Comparison of Outcomes of PHILOS for Proximal Humerus Fracture in Middle Aged Patients Based on Early Surgery vs Late Surgery - Muhammad Salman Khalil Uppal, Affan Zia Bajwa, Mirza Zeeshan Sikandar, Umair Abu Bakar Siddiq, Bilal Khan, Muhammad Abu Bakar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proximal humeral fractures are third most commonly occurring fractures of old age. PHILOS plate gives maximum fracture stabilization in the treatment of proximal humeral fractures of old age. Aim: To assess the effect of PHILOS in the management of proximal fractures of humerus and its effect on DASH scores. Methodology: A comparative cross-sectional analytical study was carried out from February to July 2022. Healing and functional outcome was assessed at 24 weeks using quick Disabilities of Arm, Shoulder and Hand score ranging from 0 to 100 where <65 reflects excellent prognosis, 65-79 means good prognosis, 80-89 satisfactory and 90-100 reflects poor prognosis. Results: A total of 106 patients volunteered in this research, with the mean age of 53.92±5.28 years, among those 92(86.79%) were males & rest 14(13.21%) were females. The patients who reported earlier have excellent prognosis when compared with those who reported after 5 days with p value .007, among those who had good response majority reported before 5 days with p value .06. Conclusion: Early presentation and prompt management of proximal humoral fractures can have better prognosis and can prevent disability. MeSh Words: Fracture, PHILOS, proximal humerus, DASH.